The efficacy, safety and clinical feasibility of a percutaneous atrial septal shunt device for pulmonary arterial hypertension: a single-center cohort study - Mingfei Li; Dandan Chen; Jianing Fan; Dan Tian; Lei Zhang; Xiaochun Zhang; Shasha Chen; Yuan Zhang; Wenzhi Pan; Lihua Guan; Daxin Zhou; Junbo Ge (Respiratory Research)
Abstract Aim To evaluate the safety and efficacy of FreeFlow percutaneous atrial septal shunt device (manufactured by AOLIU Medical Technology Co., Ltd, Shanghai, China) in patients with refractory pulmonary arterial hypertension (PAH) for the first time. Methods The study enrolled adult patients diagnosed with refractory pulmonary arterial hypertension (PAH) at the Department of Cardiology, Zhongshan Hospital, Fudan University, between Oct 2021 and Oct 2023. The patients were treated with the FreeFlow percutaneous atrial septal shunt device and underwent follow-up immediately after operation, as well as before and after discharge (at 1, 3, 6, 12 months post-operation). The primary endpoints of the study included the rate of major cardiovascular and cerebrovascular adverse events (MACCEs), serious adverse events (SAEs), and serious device-related adverse events (SADEs) within 12 months of shunt implantation. Data analysis was conducted using SAS 9.3. Results A total of 12 patients were enrolled in the study and successfully completed the operation. 10 subjects had completed 12 months’ follow-up after operation, while two subjects had died. The incidence of MACCE was 0%, and the incidence of SAEs was 33%, which was unrelated to the treatment with this device. No systemic or instrumental embolizations occurred during the follow-up period. All ten subjects exhibited a stable right-to-left shunt after the operation (100% success rate). Seven patients’ New York Heart Association (NYHA) functional classification improved from grade III to grade II. The Short Form-36 (SF-36) score and the 6-minute walking distance (6MWD) at 12 months post-operation were significantly improved compared to baseline, with scores of 47.6 ± 19.5 versus 64.7 ± 24.6 (P = 0.029) and distances of 239.5 ± 137.8 m versus 401.7 ± 129.6 m (P = 0.045), respectively. Similarly, the levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) and right heart diameter (RAD) also decreased significantly, from 3236 ± 1590.3 pg/mL to 1787.3 ± 703.7 pg/mL (P = 0.039) and from 59.1 ± 10.6 mm to 46.3 ± 7.5 mm (P = 0.046), respectively. Conclusions The results of this clinical study demonstrate that the product can attain the anticipated performance under typical conditions of use. The risks associated with the product are deemed acceptable when weighed against its potential benefits. All preclinical and clinical evaluations have furnished definitive and rational scientific evidence supporting the safety and efficacy of the percutaneous atrial septal shunt. Clinical trial number Not applicable.